Mobilisation and Bioavailability of Arsenic Around Mesothermal Gold Deposits in a Semiarid Environment, Otago, New Zealand - D. Craw; L. Pacheco (The Scientific World Journal)
Arsenopyrite (FeAsS) is the principal arsenic (As) mineral in mineralised mesothermal veins (typically 5,000 mg/kg As) in southeastern New Zealand. Groundwater in contact with arsenopyrite-bearing rocks has elevated As concentrations (up to 0.1 mg/l). The arsenopyrite decomposes slowly on oxidation in soils and historic mine workings in a cool semiarid climate. Dissolved As is predominantly As(III) in association with arsenopyrite, but this is rapidly oxidised over days to weeks to As(V) in the vadose zone. Oxidation is facilitated by particulate Fe and/or Mn oxyhydroxides, and by bacteria in surface waters. Evaporative concentration of dissolved As(V) in the vadose zone causes precipitation of scorodite (Fe(III)As(V)O4.2H2O). Adsorption of As(V) to Fe oxyhydroxides in soils and groundwater pathways lowers dissolved As concentrations. Soils over mineralised veins typically have <200 mg/kg As, as most As is removed in solution on geological time scales. Most plants on the mineralised rocks and soils do not take up As, although some inedible species can fix up to 18 mg/kg As. Hence, bioavailability of As(V) is low in this environment, despite the substantial As flux.